Melatonin Is a Feasible, Safe, and Acceptable Intervention in Doctors and Nurses Working Nightshifts: The MIDNIGHT Trial - Thottakam, Bensita M. V. J.; Webster, Nigel R.; Allen, Lee; Columb, Malachy O.; Galley, Helen F. (Frontiers in Psychiatry, 2020)
Nightshift working is associated with sleep deprivation, fatigue and attention/concentration deficits which, in healthcare workers, may impact on patient safety. Clinical staff in the UK routinely work several 12h nightshifts in a row at about 1-3 month intervals. We investigated the feasibility and acceptability of a crossover trial of melatonin administration in clinical staff working nightshifts with an exploration of effects on sleep measures and attention/concentration tasks. This was a pilot, double-blinded, randomized, placebo-controlled crossover feasibility trial in doctors and nurses working 3 consecutive nightshifts at a tertiary referral hospital in the UK. Twenty five male and female subjects were randomized to receive either 6mg CircadinTM slow release melatonin or placebo before sleep after each consecutive nightshift, followed by a washout period, before crossing over to the other experimental arm. We used actigraphy for objective assessment of sleep parameters. The trial design was feasible and acceptable to participants with negligible side effects, but elevated melatonin levels were prolonged during the active arm (P=0.016). Double digit addition testing, a concentration/attention task, improved with melatonin treatment (P<0.0001). Lapses of vigilance or judgement whilst doctors or nurses are working nightshifts could impact on patient safety and melatonin may be a useful intervention. This study supports the conclusion that a larger definitive trial of this design is both feasible and safe.